Practical formation control of multiple unicycle-type mobile robots with limited sensing ranges - Do, Khac Duc; Lau, M. (Springer Netherlands, 2011)
This paper presents a design of cooperative controllers that force a group of N unicycle-type mobile robots with limited sensing ranges to perform a desired tight formation and that guarantee no collisions between any robots in the group. The desired formation can be stabilized at any reference trajectories with bounded time derivatives. The formation control design is based on several nonlinear coordinate changes, the transverse function approach, the backstepping technique, the Lyapunov direct method, and smooth or p-times differentiable step functions. These functions are introduced and incorporated into novel potential functions to solve the collision avoidance problem without the need of switchings despite of the robots' limited sensing ranges. The proposed formation control system is applied to solve a gradient climbing problem. © Springer Science+Business Media B.V. 2011.